A review of modern approaches to the hydrodynamic characterisation of polydisperse macromolecular systems in biotechnology - Gillis, Richard B.; Rowe, Arthur J.; Adams, Gary G.; Harding, Stephen E. (Taylor & Francis, 2015)
This short review considers the range of modern techniques for the hydrodynamic characterisation of macromolecules – particularly large glycosylated systems used in the food, biopharma and healthcare industries. The range or polydispersity of molecular weights and conformations presents special challenges compared to proteins. The review is aimed, without going into any great theoretical or methodological depth, to help the Industrial Biotechnologist choose the appropriate methodology or combination of methodologies for providing the detail he/she needs for particular applications.